Details on the Hydrothermal Characteristics within a Solar-Channel Heat-Exchanger Provided with Staggered T-Shaped Baffles - Medjahed, Driss Meddah; Ameur, Houari; Rebhi, Redha; İnç, Mustafa; Ahmad, Hijaz; Menni, Younes; Aldhabani, Musaad (Mdpi, 2021)
Details on the hydrothermal characteristics of turbulent flows in a solar channel heat exchanger (CHE) are highlighted. The device has transverse T-shaped vortex generators (VGs). Two staggered VGs (baffles) are inserted on the lower and upper walls of the CHE. The working fluid is Newtonian and incompressible, with constant physical properties. The ANSYS Fluent 17.0 is utilized in this survey. The second-order upwind and QUICK schemes were utilized to perform the discretization of pressure and convective terms, respectively. The SIMPLE algorithm was employed to achieve the speed-pressure coupling. The residual target 10(-9) was selected as a convergence criterion. The effects of the T-VGs' geometrical shape and Reynolds numbers were inspected. At the baffle level, the wall effect was augmented due to the reduction of the passage area of flows, which is estimated here to be 55%, resulting thus in a considerable resistance to the movement of fluid particles. The thermal distribution is highly dependent on the flow structures within the CHE. Since the fluid agitation yields an enhanced mixing, it allows thus an excellent heat transfer. The most considerable rates of thermal transfer were obtained with high Re, which resulted from the intensified mixing of fluid particles through the formation of recirculation cells and the interaction with the walls of the T-VGs and the CHE. The T-baffles with intense flow rates yielded negative turbulent speeds and intensify the fluid agitation, which improves the thermal exchange rates.
Keywords: solar channel; heat exchanger; T-baffle; turbulence; heat transfer; hydrothermal; CFD